1990
DOI: 10.1103/physrevd.42.2626
|View full text |Cite
|
Sign up to set email alerts
|

Repulsive gravitational effects of global monopoles

Abstract: A monopole formed as a consequence of the spontaneous breakdown of a global symmetry should have a mass that grows linearly with the distance off its core. It was recently shown by Barriola and Vilenkin that the gravitational effect of this configuration is equivalent to that of a deficit solid angle in the metric, plus that of a relatively tiny mass at the origin. Here we show that this small effective mass is negative. Global monopoles thus share with other topological defects, such as domain walls and globa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
233
1

Year Published

1994
1994
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(241 citation statements)
references
References 25 publications
7
233
1
Order By: Relevance
“…Substituting eigenfunctions (17) and using the addition formula for the hyperspherical harmonics [24] …”
Section: Wightman Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Substituting eigenfunctions (17) and using the addition formula for the hyperspherical harmonics [24] …”
Section: Wightman Functionmentioning
confidence: 99%
“…However, the realistic global monopole has a characteristic core radius determined by the symmetry braking scale at which the monopole is formed. A simplified model for the monopole core where the region inside the core is described by the de Sitter geometry is presented in [17]. The vacuum polarization effects due to a massless scalar field in the region outside the core of this model are investigated in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…When gravity is taken account the linearly divergent mass of a global momopole has an effect analogous to that of a tiny mass at the origin. Harari and Loustò [3], and Shi and Li [4] have shown that this small gravitational potential is actually repulsive. Recently, Li et.al.…”
mentioning
confidence: 99%
“…The physical properties of the black-hole-global-monopole system have been studied extensively in recent years. These include, but are not limited to, the gravitational [9,10] and the vacuum polarization effects [11,12], the particle creation in the formation of the system [13], the black hole thermodynamics [14], and more recently the energy spectra of non-relativistic quantum system in the background [15].…”
Section: Introductionmentioning
confidence: 99%